Moral visions in Medieval Muslim interpretations of Sūra 102 Al-Takāthur: warnings against pride, wealth, or pleasure? - Kulinich, A (MDPI, 2022)
This article focuses on sūra 102 al-Takāthur of the Qur’ān which addresses those preoccupied with al-takāthur (competition for superiority in number, or accumulation of wealth), warning them of the punishment of Hell in the Hereafter and of their interrogation about al-na‘īm (the worldly pleasures) on the Day of Judgement. The grave eschatological implications of engaging in al-takāthur and al-na‘īm, conveyed in this sūra, have triggered attempts by Muslim scholars to determine the intended meanings of these notions and the scope of their reference. This article examines the interpretations of al-takāthur and al-na‘īm in medieval commentaries on sūra al-Takāthur with the aim of identifying and analysing various interpretative trends regarding these two notions and exploring their connection with the moral orientations among Muslims in the medieval period of Islamic history.